Рискованный рейд: художественная лит-ра / А. Гончар - Гончар Анатолий (Спецназ. Офицеры, 2012)
Экземпляры: аб. (20150715) / Инвентарный номер: 51842 / Цена: 50. 00. / Сис.шифр: Р2 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4